Soil Disinfestation Treatments with 1,3-Dichloropropene and Chloropicrin under Low Temperature Conditions for Strawberry Mother Plants - Cebolla, Vicent; Serrano, F. (2017)
Some crops do not adapt to winter disinfestation because low temperatures reduce the evaporation capacity of fumigants and its spatial distribution can't be done with the desired uniformity, and remaining phytotoxic residues need more time to be eliminated. The most problematic case in Spanish farming is on strawberry mother plants crop in highland nurseries, where disinfestation before plantation is done with soil temperatures about 10 degrees C during application. Main problems are soil fungi and the presence of weeds in springtime and summer with the mother plants still developing. In a first season were studied three new formulations of 1,3-dichloropropene 55.2% + chloropicrin 30.3% at 50 g/m(2) furnished by Agroqu micos de Levante SA., (Agrocelhone NE); methyl bromide 50% + chloropicrin 50% at 40 g/m(2) and a non disinfested check. Application has been done by shank injection, as is usually done, on mid March and crop started beginning of May. On a second season the best adjuvant was compared added or not to a set of standard mixtures of 1,3-D 36.7% and Chloropicrin 52.8%; 1,3-D 55.2% and Chloropicrin 30.3% formulated for shank injection and with emulsifiers and compared to methyl bromide. On a third season, 100 plants per plot, produced in our second season mother plant experiment, were transplanted in a commercial field at Lucena (Huelva) in order to monitor the yield, vigour and healthy state along a standard crop. The first season results showed that there are no significant differences with respect to weed control among treatments except for the check. In check treatment weeds seize the whole plot and finally plants together with weeds were eliminated. Runner production was improved by the new formulation up to the level of methyl bromide. The new formulation showed a better control of weeds than the standard mixture. On the second season, emulsifiable formulation and special formulations gave better control of weeds. On the third season no differences among treatments were found on yield and healthiness even with the check, but diameter of rhizomes on MB and especial formulations with adjuvant were significantly higher than standard formulations.